Interethnic analyses of blood pressure loci in populations of East Asian and European descent - Takeuchi, Fumihiko; Jonas, Jost B. (Nature Communications, 2018)
Blood pressure (BP) is a major risk factor for cardiovascular disease and more than 200 genetic loci associated with BP are known. Here, the authors perform discovery GWAS for BP in East Asians and meta-analysis in East Asians and Europeans and report ancestry-specific BP SNPs and selection signals.
Gesehen am 06.05.2019